Frequency Transition From Weak to Strong Turbulence in the Solar Wind - Telloni, Daniele (Frontiers in Astronomy and Space Sciences, 2022)
During a specific time window while approaching the Sun, the longitudinal speed of Parker Solar Probe matches that of the Sun's rotation. The spacecraft therefore co-rotates with the Sun, and as long as it does so, it is immersed in the solar-wind plasma of the same flow tube. This unique feature of the Parker Solar Probe's orbital configuration is exploited in this work for the first time, to investigate the spectral properties of the turbulence of the same plasma stream, from large to small scales, very close to the Sun. Standard diagnostics for spectral power, compressibility, and intermittency are applied to the magnetic field data acquired by Parker Solar Probe during its $7$th encounter with the Sun. The results clearly show the presence of a frequency transition (at about $5×10^{-3}$ Hz in the spacecraft frame) within the inertial range, where the spectrum steepens from an Iroshnikov-Kraichnan-like $3/2$ to a Kolmogorov-like $5/3$ scaling, the Alfv\'enic content decreases, whereas intermittency grows. This observational evidence is interpreted as the transition from scales dominated by Alfv\'enic fluctuations (and thus poorly intermittent and turbulent) to scales dominated by nonlinear interactions (and thus more intermittent and turbulent). To the author's knowledge, this is the first time that such a transition from weak to strong turbulence in the inertial range has been observed, and it certainly deserves further investigation, both from an observational and theoretical perspective.